Obstetrics near-miss as an indicator for maternal health care: experienced in a Malaysian tertiary hospital - AH, Habibah; Z, Huda; MJ, Amilia Afzan; T, Maiza; WH, Wan Hamilton; R, Zulida (Pink Petals Publications, 2024)
Background: Maternal near-miss known as severe maternal morbidity provides valuable information on obstetric care, hence allowing corrective action to be taken on the identified problems to reduce related morbidity and mortality. This study was conducted aiming to evaluate the maternal near-miss among women in a public tertiary hospital in Klang Valley, Malaysia. Material and Methods: A retrospective study was conducted for two years (from January 2010 until December 2011). Data were retrieved from the labour room and intensive care registry using the World Health Organization (WHO) near-miss evaluation tools based on clinical and management criteria. Results: There were 18 676 deliveries and 18531 live births with 160 near-miss cases and five maternal deaths during the study period. The prevalence of maternal near-miss morbidity was 0.86%, making maternal near-miss Ratio (MNMR) of 8.6 cases per 1,000 live births. Meanwhile, the Maternal Mortality Ratio (MMR) of 27/100 000 live births, the maternal near-miss mortality ratio (MNMMR) obtained was 32:1 and a relatively low mortality index of 3.03%. Hypertensive disorder (61.2%) and major obstetric haemorrhage (30.0%) were the two main causes of maternal near-miss morbidities followed by ICU admissions (20.6%). The hypertensive disorder primarily severe pre-eclampsia was found significantly associated with ICU utilisation (p=0.001). Conclusion: The quality of obstetric care received by maternal near-miss patients in urban Malaysia was optimal with a relatively low mortality index and comparable prevalence of maternal near-miss and mortality worldwide. Hypertensive disorders and obstetrics haemorrhage are the most common maternal morbidities in Malaysia. On top of that, sepsis is also an essential entity that needs to be emphasised in the future.